Torsion of the wandering spleen - E Kocakoc (Journal of the Belgian Society of Radiology, 2012)
Background: A 27-year-old man was admitted to our hospital with a 2-day history of abdominal pain and vomiting. The pain was non-continuous, poorly localized, and non-colicky and non-radiating in nature. Over the prior 2 months, he reported one other similar episode that had resolved spontaneously. Physical examination revealed left upper abdominal quadrant tenderness and a palpable suprapubic mass. His vital signs were stable and laboratory findings were unremarkable. Plain film of the abdomen showed gas filled bowel loops in the splenic fossa.